2015
DOI: 10.1093/jpids/piv040
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing for Diagnosis and Tailored Therapy: A Case Report of Astrovirus-Associated Progressive Encephalitis

Abstract: A boy with X-linked agammaglobulinemia experienced progressive global motor decline, cerebellar syndrome, and epilepsy. All standard polymerase chain reactions for neurotropic viruses were negative on cerebrospinal fluid and brain biopsy. Next-generation sequencing allowed fast identification of a new astrovirus strain (HAstV-VA1/HMO-C-PA), which led to tailor the patient's treatment, with encouraging clinical monitoring over 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
128
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(132 citation statements)
references
References 19 publications
4
128
0
Order By: Relevance
“…These data were corroborated in two of the cases by immunohistochemistry and in another case by in situ hybridization, localizing VA1 to neurons and astrocytes (32)(33)(34). Death occurred in four of five patients, demonstrating a high mortality rate in the reported VA1-associated cases of encephalitis (32)(33)(34)(35)(36).…”
supporting
confidence: 58%
See 2 more Smart Citations
“…These data were corroborated in two of the cases by immunohistochemistry and in another case by in situ hybridization, localizing VA1 to neurons and astrocytes (32)(33)(34). Death occurred in four of five patients, demonstrating a high mortality rate in the reported VA1-associated cases of encephalitis (32)(33)(34)(35)(36).…”
supporting
confidence: 58%
“…In these cases, all patients were immunocompromised, including three hematopoietic stem cell transplant recipients and two patients with X-linked agammaglobulinemia (32)(33)(34)(35)(36). VA1 sequences were detected in brain tissue biopsy specimens of all five cases by unbiased next-generation sequencing (32)(33)(34)(35)(36). These data were corroborated in two of the cases by immunohistochemistry and in another case by in situ hybridization, localizing VA1 to neurons and astrocytes (32)(33)(34).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…24,[46][47][48][49][50][51][52] Total RNA is extracted from a patient's CSF, and complementary DNA (cDNA) is generated by reverse transcription with random hexamer primers. The use of mNGS has gained momentum over the past several years, with several notable case reports and case series showcasing mNGS's ability to capture a broad range of infections with a single assay.…”
Section: Research Csf Metagenomic Sequencingmentioning
confidence: 99%
“…More recently, we and others have shown that improvements of the sample preparation and bioIT pipelines allow actionable diagnostics in a short and constant time. [9,10] These studies have shown the medical benefit of WG-NGS as a "last intention" test in patients who tested negative by standard diagnostic, leading to adapted therapy. In all cases, positive results were not due to the discovery of new pathogens, but to the identification of known pathogens not considered by the physicians as possible etiology or for which corresponding diagnostic tests were not available in clinical laboratories.…”
mentioning
confidence: 99%